PP-032 Design of tocilizumab desensitisation protocol after a hypersensitivity reaction. (24th February 2014) - Schwab, C; Gasperi, E; Neukirch, C; Tesmoingt, C; Arnaud, P; Arrault, X
Abstract : Background: Hypersensitivity reactions (HR) may occur after administration of monoclonal antibodies (MA). In order to avoid a switch to a less effective or potentially more toxic treatment, many desensitisation protocols (DP) exist. Mrs M, 24 years old, was hospitalised at the Bichat-Claude Bernard Hospital for Still's disease refractory to conventional treatments, namely steroids followed by methotrexate, anti-IL-1 and immunosuppressant. The fourth line treatment was not effective, and therefore treatment with tocilizumab (TZB) was started. An HR occurred (angioedema, pruritus) during the second infusion, although the drug was effective. Purpose: To design a DP for TZB. Materials and methods: To our knowledge, there is no DP for TZB in the literature. Therefore we designed a rapid DP with one bag that contained the calculated dose required for the patient's next treatment. Prior to the desensitisation, Mrs M received intravenous dexchlorpheniramine and intravenous methylprednisolone. The dose was administered at increasing infusion rate, starting at a rate of 20 mg over 2.5 h and doubling every 30 min in 5 steps, until the cumulative dose of 480 mg had been given. During the infusion, the patient was clinically monitored (blood pressure, body temperature, heart rate and oxygen saturation) every 15 min to prevent a HR. Results: The patient was clinically stable during and after the infusion: no changes of her blood pressure, body temperature, heart rate or oxygen saturation. Also, she did not develop a HR such as skin pruritus, angioedema or anaphylaxis. Conclusions: This DP differs from others by using the real patient's dose and not a standard one, the dose was administered in one bag infused continuously and the infusion rate is not fixed but was systematically doubled. Thanks to this DP, the patient will be able to continue the treatment with TZB for her Still's disease for which there are no therapeutic alternatives. No conflict of interest.